KEWENANGAN KEPALA DESA DALAM MENJALANKAN TUGAS PEMERINTAHAN BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (Studi Kasus Di Desa Simbolon Purba Kecamatan Palipi Kabupaten Samosir) - Kasman Siburian (LPPM Universitas HKBP Nommensen, 2021)
The authority and duties of the village head in running the village government are the authority and duties of the village head that must be carried out as village government. The purpose of the study was to find out, understand and explain the duties and authorities of the Village Head based on Law Number 6 of 2014 concerning Villages. To find out, understand and explain the implementation of the Duties and Authorities of the Village Head in Simbolon Purba Village, Palipi District, Samosir Regency and what obstacles are the types of this research is a juridical-empirical legal research with a descriptive analysis approach. This research was conducted using documentation techniques and interviews with parties involved in the authority and implementation of the village head's duties. The results of the study were obtained by analyzing the Shrimp Law number 6 of 2014 concerning villages by comparing the realization in the field.